Dioecy does not consistently accelerate or slow lineage diversification across multiple genera of angiosperms. Issue 3 (15th October 2015) - Sabath, Niv; Goldberg, Emma E.; Glick, Lior; Einhorn, Moshe; Ashman, Tia‐Lynn; Ming, Ray; Otto, Sarah P.; Vamosi, Jana C.; Mayrose, Itay
Summary: Dioecy, the sexual system in which male and female organs are found in separate individuals, allows greater specialization for sex‐specific functions and can be advantageous under various ecological and environmental conditions. However, dioecy is rare among flowering plants. Previous studies identified contradictory trends regarding the relative diversification rates of dioecious lineages vs their nondioecious counterparts, depending on the methods and data used. We gathered detailed species‐level data for dozens of genera that contain both dioecious and nondioecious species. We then applied a probabilistic approach that accounts for differential speciation, extinction, and transition rates between states to examine whether there is an association between dioecy and lineage diversification. We found a bimodal distribution, whereby dioecious lineages exhibited higher diversification in certain genera but lower diversification in others. Additional analyses did not uncover an ecological or life history trait that could explain a context‐dependent effect of dioecy on diversification. Furthermore, in‐depth simulations of neutral characters demonstrated that such bimodality is also found when simulating neutral characters across the observed trees. Our analyses suggest that – at least for these genera with the currently available data – dioecy neither consistently places a strong brake on diversification nor is a strong driver.